How Radical Is Embodied Creativity? Implications of 4E Approaches for Creativity Research and Teaching - Laura H. Malinin (Frontiers in Psychology, 2019)
Modern ideas of embodiment have been influential in cognitive science for the past several decades, yet there is minimal evidence of embodied cognition approaches in creativity research or pedagogical practices for teaching creativity skills. With creativity research in crisis due to conceptual, methodological, and theoretical issues, radical embodied cognitive science (RECS) may offer a framework to move the field forward. This conceptual analysis examines the current state of creativity research from the 4E (embodied, embedded, enactive, and extended) cognition and RECS perspectives. Two streams are critiqued for their potential to further knowledge about the development of creative expertise and inform educational practices. Promising directions for future research is discussed, including ways dynamical systems approaches, such as those used in improvisational and musical creativity, might yield new insights about how people develop creative expertise and help address the “higher order thinking” criticisms of RECS.